Corrosion behaviour of a quenched and partitioned medium carbon steel in 3.5 wt.% NaCl solution. (January 2018) - Yang, Jilan; Lu, Yufei; Guo, Zhenghong; Gu, Jianfeng; Gu, Caixiang
Highlights: Corrosion characteristics of quenched and partitioned steel are determined. Quenched and partitioned steel specimens are immersed in a NaCl solution. Retained austenite increases the corrosion potential of a martensitic matrix. All studied steel samples exhibit similar corrosion variation trends. Abstract: In this work, the corrosion characteristics of a quenched and partitioned (Q&P) medium carbon steel in a 3.5 wt.% NaCl solution were investigated by various surface analysis techniques and then compared with those of the quenched and tempered steel with the same composition. Both steels exhibited nearly identical corrosion variation trends. However, the Q&P specimen demonstrated a lower corrosion rate. The formation of retained austenite in the carbon-enriched state increases the corrosion potential of the carbon-depleted martensitic matrix and decreases the residual tensile stress on the Q&P surface, thus enhancing its corrosion resistance.